Le hasard dans la science-fiction - Jean-Luc Gautero (Cahiers de Narratologie)
Chance plays a major part in many works of science-fiction. This paper tries to study the main themes to which it is connected, while focusing on some texts and relating its use to some important issues of history and philosophy of probability theory.